2021
DOI: 10.3390/rs13193986
|View full text |Cite
|
Sign up to set email alerts
|

Increased Ecosystem Carbon Storage between 2001 and 2019 in the Northeastern Margin of the Qinghai-Tibet Plateau

Abstract: Global alpine ecosystems contain a large amount of carbon, which is sensitive to global change. Changes to alpine carbon sources and sinks have implications for carbon and climate feedback processes. To date, few studies have quantified the spatial-temporal variations in ecosystem carbon storage and its response to global change in the alpine regions of the Qinghai-Tibet Plateau (QTP). Ecosystem carbon storage in the northeastern QTP between 2001 and 2019 was simulated and systematically analyzed using the Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
(71 reference statements)
0
12
0
Order By: Relevance
“…However, research also indicates that LUCC of terrestrial ecosystems has become an important source of carbon emissions, which is second only to the burning of fossil fuel 8 , 9 . Research on changes in carbon storage based on LUCC has become one of the main methods for monitoring ecosystem service function 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, research also indicates that LUCC of terrestrial ecosystems has become an important source of carbon emissions, which is second only to the burning of fossil fuel 8 , 9 . Research on changes in carbon storage based on LUCC has become one of the main methods for monitoring ecosystem service function 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The InVEST model provides new technology for conducting spatial expression, dynamic analysis, and quantitative evaluation of ecosystem service function 14 . More importantly, the InVEST model can easily be used to assess the impact of climate and LUCC changes on ecosystem carbon storage 11 . Changes in LUCC alter the structure (biomass, species composition) and function (energy balance, carbon cycle, biodiversity) of the ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have utilised the InVEST model to evaluate the status of C reserves in regional ecosystems. For example, Wei et al (2021) performed a systematic study on C stocks in the northeastern Qinghai-Tibet Plateau (QTP) (P. Wei et al 2021). However, this only re ected the changes in regional ecological C stocks and it was lack of basis for predicting future trends in C stocks or the future management of C pools and policy formulation.…”
Section: Deng Et Al 2016)mentioning
confidence: 99%
“…LUCC can also alter the process of C cycling by changing the structure and function of ecosystems (P. Wei et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Establishing relationships between VIs and recorded AGB is the most common and direct approach for regional grassland AGB assessment. Many studies have reported that there is a strong correlation between the VIs, including normalized difference vegetation index (NDVI; Wei et al, 2021), enhanced vegetation index (EVI; Ge et al, 2018), soil adjusted vegetation index (SAVI; Ren et al, 2018), ratio vegetation index (RVI; Guerschman et al, 2009) and biomass in varies satellite images. However, VIs are subjected to the influence of environmental condition and the capability of characterizing vegetation status in certain circumstance, which can introduce errors and uncertainties into AGB estimation (Ali et al, 2016).…”
Section: Introductionmentioning
confidence: 99%